# Given #f(n)=n-4# and #g(n)=2n#, how do you find #3f(n)+5g(n)#?

By signing up, you agree to our Terms of Service and Privacy Policy

To find 3f(n) + 5g(n), substitute the functions f(n) and g(n) into the expression and perform the calculations:

3f(n) = 3(n - 4) 5g(n) = 5(2n)

Now, expand and simplify each term:

3(n - 4) = 3n - 12 5(2n) = 10n

Finally, add the two terms together:

3f(n) + 5g(n) = (3n - 12) + (10n) = 3n + 10n - 12 = 13n - 12

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7